Fluid Mechanics Lab Manual - Ashish Kumar Parashar (Fluid Mechanics Lab Manual, 2022)
Fluid Mechanics is the branch of science that studies the fundamental behavior of fluids when they are in state of motion or rest. Whether the fluid is at rest or motion, it is subjected to different forces and different climatic conditions and it behaves in these conditions as per its physical properties. Fundamental acquaintance about fluid mechanics is required in various areas such as water resources engineering, hydraulic engineering environmental engineering, geotechnical engineering and structural engineering. The Fluid Mechanics laboratory is actively engaged to strengthen and enhance, understanding and knowledge of civil engineering students about the experimental methods and its basic principle and apply those concepts in practice. The Fluid Mechanics lab is equipped with different flow measuring set-ups for pipe, channel such as venturimeter, orificemeter, notches, orifice and mouthpiece, where students can visualize the basic theory of working of equipments. For performing the experiments in the laboratory a lab manual is necessary. The present lab manual provides students with an overview of thirteen different fluid mechanics laboratory experiments and their practical applications. The lab manual contains objective, methods, theory, equipments required to perform experiments which helps the students to prepare their lab records. The present lab manual helps the students not only for conducting experiments, but also in viva –voce exam.